Analysis of Expressive Dislike and Sorrow in Death Penalty Murder Case Reports : Forensic Linguistics - Fifi Safreni; Burhanuddin Arafah; M. Manugeren (International Journal of English and Applied Linguistics (IJEAL), 2025)
The purpose of this research is to identify expressions of dislike and sorrow from the perpetrator of the murder in the case of Judge Jamaluddin's murder. The murder by Zuraida Hanum and two other perpetrators was motivated by deep dislike, insult, and revenge. Forensic Linguistics, as an applied language science, is used to analyze language and law scientifically in messages and statements related to crime case reports. The theory used is expressive speech acts from pragmatics by Searle in Yule. A qualitative descriptive method was used with data collection procedures related to the research topic. Expressive Speech Acts and feeling of trauma from Sigmund Freud's theory of impersonation trauma, interpersonal trauma, and attached trauma helps in comprehensively understanding the meaning of expressions, specifically focusing on dislike and sorrow as the causal relationship explained in detail. This research takes sentences from primary data sources in the form of court decisions and secondary data sources from books, journals, and current news. Findings of expressive acts and trauma thus conclude that the expressive speech acts experienced by the perpetrator are significant, including dislike and sorrow, and interpersonal trauma of the perpetrator dominates the reporting of this murder case.